Dried venous blood samples for the detection and quantification of measles IgG using a commercial enzyme immunoassay - Riddell Michaela A.; Byrnes Graham B.; Leydon Jennie A.; Kelly Heath A. (The World Health Organization, 2003)
OBJECTIVES: To determine whether samples of dried venous blood (DVB) were an acceptable alternative to serum for detecting measles-specific IgG in a commercial enzyme immunoassay. METHODS: Paired samples of serum and DVB were collected from 98 suspected cases of measles and 1153 schoolchildren in Victoria, Australia. All samples were tested using the Dade Behring Enzygnost® Anti-Measles-Virus/IgG immunoassay. DVB samples were eluted using either the sample buffer provided with the kit or 5% dry milk powder in phosphate-buffered saline-Tween 20. FINDINGS: DVB samples eluted by sample buffer showed significantly better linear correlation to the serum samples than did DVB samples eluted in 5% dry milk in phosphate-buffered saline-Tween 20. To improve the comparability of serum and DVB samples an adjustment factor of 1.28 was applied to the optical density (OD) values of DVB. This adjustment also enabled quantification of the titre of measles IgG in mIU/ml directly from the OD value using the alpha calculation as specified by the kit protocol. For DVB samples stored for less than six months at 4 °C, the assay showed an overall sensitivity of 98.4% and a specificity of 97.2% compared with the results of serum testing. CONCLUSION: These results illustrate the potential for DVB samples to be widely used with the Dade Behring enzyme immunoassay system for determining the immunity of the individual and the population to the measles virus.